The Solar Orbiter magnetometer - Horbury TS; O'Brien H; Blazquez IC; Bendyk M; Brown P; Hudson R; Evans V; Oddy TM; Carr CM; Beek TJ; Cupido E; Bhattacharya S; et al. (EDP SCIENCES S A, 2022)
The magnetometer instrument on the Solar Orbiter mission is designed to measure the magnetic field local to the spacecraft continuously for the entire mission duration. The need to characterise not only the background magnetic field but also its variations on scales from far above to well below the proton gyroscale result in challenging requirements on stability, precision, and noise, as well as magnetic and operational limitations on both the spacecraft and other instruments. The challenging vibration and thermal environment has led to significant development of the mechanical sensor design. The overall instrument design, performance, data products, and operational strategy are described.